Clinical effectiveness and cost-effectiveness of physiotherapy and occupational therapy versus no therapy in mild to moderate Parkinson’s disease : a large pragmatic randomised controlled trial (PD REHAB) /: a large pragmatic randomised controlled trial (PD REHAB). (August 2016) - Clarke, Carl E
No abstract available